Mitochondrial polymorphisms associated with differential longevity do not impact lifetime-reproductive success - Castri, Loredana (2010)
Objective: To determine if individuals who carry mitochondrial markers which have been previously shown to affect longevity also have differential lifetime reproductive success (LRS). Methods: We extracted the mtDNA from living subjects residing in Atenas, Costa Rica. Since mtDNA does not recombine, and its probability of mutation is low, we assume that all maternal ancestors of the living subjects have the same mtDNA. We reconstructed the maternal genealogy of the living subjects, so that we have information on the LRS and longevity of the maternal ancestors of the living subjects. We compared the LRS of women who carried the 5178A marker in haplogroup D (associated with decreased longevity) and who carried the 150T polymorphism (associated with increased longevity) with the LRS of controls born in the same half century time period from 1750 to 1939. Results: We found that the LRS of neither group of women with a longevity-associated polymorphism (LAP) differed from the LRS of controls, even if these women differed signiﬁcantly from the controls in their longevity. Conclusions: Although LAPS signiﬁcantly affect longevity, such differential longevity does not result in differential lifetime reproductive success. From an evolutionary perspective, these longevity-associated polymorphisms do not affect the carriers’ Darwinian ﬁtness.